Recent advances and applications of optical coherence tomography angiography in diabetic retinopathy - Zhang, Qing; Gong, Di; Huang, Manman; Zhu, Zhentao; Yang, Weihua; Ma, Gaoen (Frontiers in Endocrinology, 2025)
IntroductionOptical coherence tomography angiography (OCTA), a noninvasive imaging technique, is increasingly used in managing ophthalmic diseases like diabetic retinopathy (DR). This review examines OCTA’s imaging principles, its utility in detecting DR lesions, and its diagnostic advantages over fundus fluorescein angiography (FFA).MethodsWe systematically analyzed 75 articles (2015–2024) from the Web of Science Core Collection, focusing on OCTA’s technical principles, clinical applications in DR diagnosis, and its use in diabetes mellitus (DM) without DR and prediabetes. The use of artificial intelligence (AI) in OCTA image analysis for DR severity evaluation was investigated.ResultsOCTA effectively identifies DR lesions and detects early vascular abnormalities in DM and prediabetes, surpassing FFA in noninvasiveness and resolution. AI integration enhances OCTA’s capability to diagnose, evaluate, and predict DR progression.DiscussionOCTA offers significant clinical value in early DR detection and monitoring. Its synergy with AI holds promise for refining diagnostic precision and expanding predictive applications, positioning OCTA as a transformative tool in future ophthalmic practice.